The Development of an Image Classification Application. - Baradaran-Syed, Taranch (1996)
Keywords: dept.csc; faculty_collection; sabbatical_report

Experiences in parallel/distributed computing for undergraduate computer science majors - Parikh, J.A. (ASEE Annual Conference Proceedings, 1996)
The increasing prevalence of multiprocessor and distributed systems in modern society is making it imperative to introduce the underlying principles of parallel/distributed computing to students at the undergraduate level. In order to meet the needs of our students for training in this critical area, the Computer Science Department at Southern Connecticut State University (SCSU) is currently in the process of implementing a curricular and laboratory development project that integrates key concepts and practical experiences in parallel computing throughout the undergraduate curriculum. The goal of this project is to build a strong foundation in parallel computing which would optionally culminate in advanced, senior-level specialized courses in parallel computing and/or senior research projects. This paper describes the laboratory facility we developed to support instruction in parallel and distributed computing and the parallel computing modules which were incorporated into three of our core undergraduate courses: data structures, operating systems, and programming languages. The laboratory facility enables us to provide our students with "hands-on" experiences in shared memory, distributed memory, and network parallelism. The modules and laboratory exercises give students the opportunity to experiment with a wide array of software and hardware environments and to gain a systematic exposure to the principles and techniques of parallel programming.
Journal Abbreviation: ASEE Annu. Conf. Proc.
Keywords: Computer operating systems; Computer science; Computer software; Curricula; Distributed computing; Engineering education; Node configurations; Parallel processing systems; Parallel programming; Professional aspects; Project management; Social aspects; Software configurations; Students; Teaching; dept.csc